2016
DOI: 10.21608/ajs.2016.14428
|View full text |Cite
|
Sign up to set email alerts
|

RESPONSE OF POT MARIGOLD (Calendula officinalis L.) TO DIFFERENT APPLICATION METHODS AND CONCENTRATIONS OF SEAWEED EXTRACT

Abstract: This research study was carried out in the open field during the two successive seasons of 2012/2013 and 2013/2014. The aim of this investigation was to study the response of pot marigold (Calendula officinalis L.) to different application methods and concentrations of seaweed extracts applied as a commercial compound. Seven treatments were initiated, i.e. three concentrations of seaweed extracts (500, 1000, 1500) were used either as foliar spray or as soil drench in addition to the control treatment (tap wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…Secondly, the continuous supply of nutrients and growth-promoting compounds through drenching stimulates lateral branching and encourages the plants to produce more side shoots, resulting in a fuller and more expansive plant spread. The findings of the present investigation are in conformity with the reports of Tartil et al, [16] in pot marigold; Karim et al, [11] and El-Hady [12] in Tuberose; Sohier et al, [13] in Dahlia; Sumangala et al, [6] and Kularthne et al, [7] in rose; Alhasan et al, [8] in gerbera; Zelikovic et al [9] in pansy; Tiwari et al, [10] in wheat.…”
Section: Plant Spread and Number Of Branches Per Plantsupporting
confidence: 92%
“…Secondly, the continuous supply of nutrients and growth-promoting compounds through drenching stimulates lateral branching and encourages the plants to produce more side shoots, resulting in a fuller and more expansive plant spread. The findings of the present investigation are in conformity with the reports of Tartil et al, [16] in pot marigold; Karim et al, [11] and El-Hady [12] in Tuberose; Sohier et al, [13] in Dahlia; Sumangala et al, [6] and Kularthne et al, [7] in rose; Alhasan et al, [8] in gerbera; Zelikovic et al [9] in pansy; Tiwari et al, [10] in wheat.…”
Section: Plant Spread and Number Of Branches Per Plantsupporting
confidence: 92%
“…Similar findings have been reported in previous studies conducted on various plant species, including marigold by Russo et al [23], chrysanthemum by Hegde et al [15] and Bhargavi et al [22], pot marigold by Tartil et al [16], rose by Praveen et al (2020), and Chinese carnation and Gazania splender by Majeed Khadim Al-Hamzawi [24].…”
Section: Flower Yield Parameterssupporting
confidence: 89%
“…Similar findings have been reported by Russo et al [23] in marigold, Pruthvi et al [25] in chrysanthemum, Tartil et al [16] in pot marigold, Bhargavi et al [22] in chrysanthemum, Praveen et al [18] in rose, and Majeed Khadim Al-Hamzawi [24] in Chinese carnation and Gazania splender. Their studies also demonstrated the positive effects of treatments on flower yield, emphasizing the importance of vegetative growth and photosynthate utilization in maximizing flower production.…”
Section: Flower Yield Parameterssupporting
confidence: 86%
See 2 more Smart Citations